Advokasi Sosial Berbasis Asset Based Community Development dalam Mewujudkan Inklusi Sosial Melalui Promahadesa pada Kedai Susu Tuli (K-SULI) - Siti Maimunatul Kamilah Rohman; Imroati Khonita; Niken Puspitasari; Akbil Mastufatul Farihah; Safira Nuris Samsil Mufidah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Kedai Susu tuli (K-SULI) are sociopreneurship that located in Jember Regency. K-SULI serves as a place for a tuli person, or those knows as hearing difable to develop their entrepreneurial skills. through direct practice. K-SULI also became a place to community service program carried out by Program Mahasiswa Berdesa 2024 (Promahadesa) team of Jember University, aimed at introducing deaf culture particularly sign language in transactional activities. The Promahadesa team conduct their community services using the Asset Based Community Development (ABCD) approach, a community empowerment that leverage K-SULI potencial to implements. The result of this initiative taken Promahadesa include the expansion of K-SULI partnership, recruitment and training of employees, development of standart operation for transaction (SOPT), product Innovation, both offline and online social marketing, and introduction for sign language through Belajar Bahasa Isyarat Asik (BERBISIK).